Peroxisomal Membrane Contact Sites in Mammalian Cells - Chen, Chao; Li, Jing; Qin, Xuhui; Wang, Wei (Frontiers in Cell and Developmental Biology, 2020)
Peroxisomes participate in essential cellular metabolic processes, such as oxidation of fatty acids (FAs) and maintenance of reactive oxygen species (ROS) homeostasis. Peroxisomes must communicate with surrounding organelles to exchange information and metabolites. The formation of membrane contact sites (MCSs), where protein-protein or protein-lipid complexes tether the opposing membranes of two organelles, represents an essential means of organelle crosstalk. Peroxisomal MCS (PO-MCS) studies are emerging but are still in the early stages. In this review, we summarize the identified PO-MCSs with the ER, mitochondria, lipid droplets, and lysosomes in mammalian cells and discuss their tethering mechanisms and physiological roles. We also highlight several features of PO-MCSs that may help future studies.